Exploiting asymmetric wire critical current for the reduction of AC loss in HTS coil windings. (26th September 2019) - Jiang, Zhenan; Endo, Natsumi; Wimbush, Stuart C; Brooks, Justin; Song, Wenjuan; Badcock, Rodney A; Miyagi, Daisuke; Tsuda, Makoto
Abstract: Critical current and AC loss in coil windings are two important factors for various HTS applications. Many coated conductors exhibit asymmetry in the variation of the critical current with magnetic field angle. This asymmetry results in different coil critical current values depending on the orientation of the conductors in the coil windings. We report critical current and AC loss results at 77 K and 65 K for three hybrid coil assemblies which have a common central winding and different arrangements of the end windings. We found a difference greater than 13% in both the critical current and the AC loss results for the different arrangements. The results imply that if we wind coil assemblies smartly even using the same materials and the same design, we can not only improve critical current but also reduce AC loss significantly.